Implementasi Kebijakan Ekonomi Syariah dalam Sistem Perbankan di Indonesia - Putra, Aldi Febriansa; Zulfa, Aini Yatuz; Nurwahyudi, Raulindo Putra; Koto, M. Alif Hakam; Hidayatullah, Gin Gin Farid; Salam, Muhammad Ridwan; Herdiana, Dian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The growth of Islamic banking in Indonesia reflects the increasing public interest in an Islamic economic system that is fair, transparent, and free from interest (riba). Along with regulatory support from the government and financial authorities, the implementation of sharia economic policies has become an important instrument in strengthening the position of Islamic banking amidst the dominance of the conventional banking system. This study aims to examine the form of policy implementation, supporting and inhibiting factors, as well as the effectiveness of sharia economic policies in driving the growth of this sector. The research method uses a descriptive qualitative approach based on secondary data, with analysis conducted on regulations through literature study techniques. The results show that although the policies have had a positive impact on the growth of Islamic banks, significant challenges remain in the areas of literacy, human resources, and service access distribution. Therefore, synergy between the government, the OJK (Financial Services Authority), and educational institutions is key to strengthening the foundation of inclusive and sustainable Islamic banking